2021
DOI: 10.5114/ain.2021.107709
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-related knowledge and attitudes as predictors of drinking behaviours among Portuguese university students

Abstract: No ghostwriting and guest authorship declared./Nie występują zjawiska ghostwriting i guest authorship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 76 publications
(103 reference statements)
1
3
0
Order By: Relevance
“…During the COVID-19 pandemic, the perception of peers’ changes in alcohol-related behaviour is strongly linked to changes in students’ own alcohol use, and this fact needs to be taken into account when developing effective strategies and prevention programs [ 62 ]. This agrees with the results of Alves et al [ 63 ], who found that current residence, drinking peers, alcohol-related knowledge and attitudes about alcohol have a statistically significant effect on the probability of developing a risky pattern of alcohol use among university students. This can also explain the discrepancy between results in the Czech Republic and the Slovak Republic.…”
Section: Discussionsupporting
confidence: 93%
“…During the COVID-19 pandemic, the perception of peers’ changes in alcohol-related behaviour is strongly linked to changes in students’ own alcohol use, and this fact needs to be taken into account when developing effective strategies and prevention programs [ 62 ]. This agrees with the results of Alves et al [ 63 ], who found that current residence, drinking peers, alcohol-related knowledge and attitudes about alcohol have a statistically significant effect on the probability of developing a risky pattern of alcohol use among university students. This can also explain the discrepancy between results in the Czech Republic and the Slovak Republic.…”
Section: Discussionsupporting
confidence: 93%
“…More recent studies (Alves et al, 2021;Lategan et al, 2017;Nyandu & Ross, 2020) argue that a better understanding of the drinking behaviour of university students is essential to address the drinking-related challenges. Additional insights into drinking behaviour can be gained by investigating various socio-demographic groups (WHO, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The conducted research on the level of consumers' knowledge of the impact of ethanol on health concerns mainly specific professional groups [30,31] or focuses on the analysis of women's knowledge in various physiological states [32] and is often conducted on small population groups that cannot be considered representative [33,34].…”
Section: ■ Introductionmentioning
confidence: 99%
“…Analysing the research conducted in different regions of the world, it was observed that consumers' general knowledge of alcoholic beverages is low [32][33][34][35], only a small percentage of respondents are aware of the existence of guidelines on the amount of ethanol consumed considered to be safe [31,35], most respondents cannot estimate the energy value of alcoholic beverages [35,36] or cannot indicate the symptoms of ethanol dependence [37] and possible risks of its excessive consumption [34,36]. Due to the observed gaps in knowledge and misconceptions about the impact of ethanol on health, an attempt was made to compare the level of knowledge and beliefs of consumers of alcoholic beverages from different regions of the world regarding the impact of ethyl alcohol on health.…”
Section: ■ Introductionmentioning
confidence: 99%